Factors Related to Oncologists’ Use of the Disease Treatment and Employment Support Guidance Fee - SASAKI, Jiichiro; EGUCHI, Hisashi; INOUE, Akiomi; TATEISHI, Seiichiro (Journal of UOEH, 2021)
The purpose of this study is to examine the factors related to oncologists’ use of the disease treatment and employment support guidance fee in Japan. A cross-sectional online survey was conducted in January 2021 among all the diplomates of the subspecialty board of medical oncology in the Japanese Society of Medical Oncology (n = 1,452), using the official mailing list. Logistic regression analysis was used to investigate the association between demographic and other factors and use of the disease treatment and employment support guidance fee. In total, 146 individuals participated in the study (response rate 10.0%). Experience of using the fee was associated with medical specialty and knowledge of the Guideline for Workplace Patient Coordination and Disease Treatment. It may be possible to increase the use of the disease treatment and employment support guidance fee among oncologists by raising awareness of the Guideline for Workplace Patient Coordination and Disease Treatment.